Novel outreach settings to enhance sexually transmitted infection/HIV awareness, diagnosis and treatment in hard-to-reach populations. (March 2018) - Lampejo, T; Turner, R; Roberts, C; Allen, K; Watson, L; Caverley-Frost, L; Scott, P; Ostridge, E; Cooney, G; Hardy, J; Nulty, K; Day, S
Despite recent rises in the number of cases of sexually transmitted infections (STIs) such as syphilis and gonorrhoea in England and increasing rates of HIV diagnosis among several men who have sex with men populations, many individuals are still not engaging with sexual health services. The John Hunter Clinic for Sexual Health, Chelsea and Westminster Hospital, London set up outreach clinics at the two world's largest adult lifestyle exhibitions in 2013 and 2015. This was the first time that a sexual health screening and promotion service was available at these large-scale (over 10, 000 attendees at each) adult lifestyle events. A total of 381 individuals underwent STI screening across the two events. Nineteen (5.0%) patients were diagnosed with an infection. Twelve (3.1%) patients with Chlamydia trachomatis, three (0.8%) patients with syphilis, one (0.3%) patient with Neisseria gonorrhoeae, one (0.3%) patient with HIV, one (0.3%) patient with hepatitis B and one (0.3%) patient with hepatitis C. All 19 patients were promptly contacted with their results and had arrangements made for treatment or were referred for specialist follow up. Where possible, contact tracing was also performed. Implementing such outreach-based projects is challenged by lack of on-site laboratory support, high staffing demands and potentially high costs. However, we achieved a total HIV screening uptake rate of 94.5% amongst our outreach clinic attendees (versus 67% nationally in conventional sexual health clinic attendees) with an HIV positivity rate of 0.3% (versus 0.2% nationally in high HIV prevalence band populations). Additionally, 30.7% had never been tested for HIV previously (versus 20.7% nationally). Our work demonstrates that these strategies can help to address issues related to lack of STI/HIV screening in hard-to-reach populations and promote risk reduction behaviour.